ANALISIS KETIMPANGAN PENDAPATAN USAHATANI JAGUNG DI KECAMATAN PULUBALA KABUPATEN GORONTALO - Sinyin Dalila; Mahludin Baruwadi; Irwan Bempah (Universitas Negeri Gorontalo, 2018)
This study aims to analyze: 1) Analyzing income inequality that occurs in corn farmers in District Pulubala Gorontalo District, 2) To analyze income outside corn farming on income inequality of corn farmers in District Pulubala Gorontalo regency. This research was conducted in four villages which became observation area in Pulubala District of Gorontalo Regency from August until November of 2017. The method used was survey method that is data collection based on interview and observation. The sampling technique is done by using simple random sampling method, which is random sampling from all population located in District Pulubala Gorontalo Regency where in this study population consists of 100 respondents farmers and taken multiples 2 so that the sample obtained as many as 50 people. Types and data sources used in this study are primary data and secondary data. Analysis of data used to calculate the level of income inequality using the formula Gini Ratio figure. The results showed that: 1) The income of corn farmers in District Pulubala sourced from corn farming alone is in the category of low lenght is 0.173 or 0.3. 2) Other income outside maize farming has an effect on inclination trend of household income of farmer where there is decreasing income inequality. This can be seen from the Gini Ratio figures obtained from the income of all farms that is equal to Gini Ratio = 0.167 and for Gini Ratio ratio of all household income of Gini Rasio = 0, 161.